ANALISIS EFEKTIVITAS PAJAK DAERAH ATAS PENDAPATAN ASLI DAERAH PADA BADAN PELAYANAN PAJAK DAERAH KOTA MALANG TAHUN 2011-2016 - Yunita Dwi Puspita; Nur Hidayati; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2017)
AbstractThe purpose of this study is to determine the effectiveness of local taxes of the Cityreal income in Malang on 2011-2016. The Research conducted at the Regional Tax Service(BP2D) Malang. The research method using descriptive research, data analysis method usedis quantitative method with secondary data. The research Conducted to measure aphenomenon of research by using the indicator of regional financial ratios to obtain anoverview of local tax revenue mechanisms on City real income (PAD) in order to achieveregional independence. The results of the analysis show that the level of effectiveness of localtaxes during the period of six years varies. The highest effectiveness rate in 2012 was 126%and in 2014 has the lowest effectiveness of 108%. Then the highest percentage When viewedfrom each local taxis from Entertainment taxes in 2012 which reached 159% and local taxesthat have the lowest percentage rates during the year of 2012-2016 from the advertisementtax in 2011 by 94% when compared with the other years . The low level of advertisement taxrate in 2011 was due to the fact that in 2011 the tax targets charged were higher whichcaused the realization of advertisement tax could not reach the good target.Keywords: Effectiveness, Local Tax, City real Income